Gynecological Surgery puerperal gravid state - Achard, Arturo (2015)
The author shows the effects of pregnancy on fibromyomas. The increase in size in relationship principally with edema or on the basis of degenerative changes. Aside from enlargement he emphasized the importance of degenerative changes, especially the so called "red degeneration" as one of the most serious changes. The large fibroids may be incarcerated in the pelvis, some times respond to the upward traction. The effects of myomas in pregnancy are variable, women with such tumors are frequently sterile. It is best, whenever possible, to wait and watch before operating, and if be visles to do so the surgeon must keep in mind the present conditions after the laparotomy. In any case, the surgical will be conservative. He made the myomectomy with the intermitent Borras procedure. Sometimes it is necessary to practice the hysterectomy. The repair will be by planes. To avoid the bleeding in many cases is valuable to put temporary ligatures. Antibiotics and drainage in the abdominal cavity. When the pregnancy is complicated by ovarian tumors the difficulties become present the later months of pregnancy. Indications for inmediate operation in pregnancy are: suspicion of malignant, torsion of the pedicle, signs of infection and overdistention of the abdomen, etc.